Jaspers’ Concept of the University - Burch, Robert (Canadian Journal of Higher Education, 1976)
The paper has a threefold purpose. The first is simply expository: it outlines and explicates the general character of Jaspers' notion of the idea of the university, and seeks to do so in such a way as to make this notion more readily intelligible to readers unfamiliar with Jaspers' philosophy as a whole. To this end, it elucidates the essential content of the notion, clarifies what is meant here by the term "idea", illumines the essential philosophic foundations up-on which Jaspers' discussion is based and traces out the systematic structure of his position. Secondly, the paper states a number of basic objections to Jaspers' view, and in most cases, through the extrapolation of his explicit remarks, is able to suggest how Jaspers himself might have responded to these objections. The purpose of this discussion, however, is not principally to resolve the issues raised, but simply to open the way for genuine debate. Thirdly, throughout the paper the attempt is made, both explicitly and implicitly, to establish the relevance of Jaspers' work to current university problems. This is accomplished on two levels: the first emphasises the importance per se of continued reflection on the idea of the university as the means of gaining needed clarity regarding both the true nature and mission of the university and the ultimate significance of our commitment to this in- stitution; and the second indicates how Jaspers' particular judgements concerning this first matter bear directly upon more specific issues, e.g. the relation of teaching and research, academic standards, university autonomy, the essential responsibilities of professors and students, etc. Implicit to this threefold intention is the conviction that philosophic reflection on the idea of the university is vital to the institution's authentic existence, and that Jaspers' own work in this area is at present unrivalled in its breadth of vision and profundity. It is thus hoped that the paper will lead its readers to a more serious consideration of Jaspers' work, and from there, once they perceive what is really at stake, to a reflection on the issue itself - the idea of the university.